The Indian Ocean and its implications for a Global Intellectual History of Political Economy - Steardo, Mattia (TSEG - The Low Countries Journal of Social and Economic History, 2020)
Books under review: Johan Mathew, Margins of the Market. Trafficking and Capitalism across the Arabian Sea (Oakland, CA: University of California Press, 2016) Fahad A. Bishara, A Sea of Debt. Law and Economic Life in the Western Indian Ocean, 1780-1950 (Cambridge: Cambridge University Press, 2017) Tariq O. Ali, A Local History of Global Capital. Jute and Peasant Life in the Bengal Delta. (Princeton, NJ: Princeton University Press, 2018)